Pedagogy in Strengthening Visual Perception: A Review of the Literature - Baldeón, Claudio Percy Hurtado; Fuster-Guillén, Doris; Figueroa, Roger Pedro Norabuena; Lirio, Rudecindo Albino Penadillo; Hernández, Ronald M. (Indian Journal of Information Sources and Services, 2024)
The objective of this study is to know the educational intervention practices that strengthen visual perception in elementary school students, for that reason we went to the review of various bibliographic sources managing to locate 44 original scientific articles plus a doctoral thesis in different languages between the years 2012 and 2022; belonging to countries such as: Ecuador, Colombia, Cuba, Spain, Peru, Argentina, Mexico, United States, El Salvador, Costa Rica and Saudi Arabia. Likewise, the bibliographic location was carried out in Scopus, Scielo, Redalyc, Dialnet, EDUSER, Researchgate and RCM journals; using different search strategies: keyword, topic and/or follow-up of the bibliography of a base document. After an analysis of the theories, it can be mentioned that pedagogical praxis are important to strengthen perception skills in school-age students, concluding that if they are accompanied by strategies and the use of digital resources, they overcome the deficiencies within a learning process in the classroom.